Investigating the need for alcohol harm reduction and managed alcohol programs for people experiencing homelessness and alcohol use disorders in Scotland. (1st October 2020) - Carver, Hannah; Parkes, Tessa; Browne, Tania; Matheson, Catriona; Pauly, Bernie
Abstract: Introduction and Aims: Managed alcohol programs (MAP) are a harm reduction approach for those experiencing alcohol use disorders (AUD) and homelessness. These programs were developed in Canada and have had positive results; very few exist in the UK and Ireland. The aim of this study was to scope the feasibility and acceptability of implementing MAPs in Scotland. Design and Methods: Using mixed‐methods, we conducted two linked phases of work. Quantitative data were collected from the case records of 33 people accessing eight third sector services in Scotland and analysed in SPSS using descriptive and inferential statistics. Qualitative data were collected in Scotland via semi‐structured interviews with 29 individuals in a range of roles, including strategic informants ( n = 12), service staff ( n = 8) and potential beneficiaries ( n = 9). Data were analysed using Framework Analysis in NVivo. Results: The case record review revealed high levels of alcohol use, related health and social harms, illicit drug use, withdrawal symptoms, and mental and physical health problems. Most participants highlighted a lack of alcohol harm reduction services and the potential of MAPs to address this gap for this group. Discussion and Conclusions: Our findings highlight the potential for MAPs in Scotland to prevent harms for those experiencing homelessness and AUDs, due to high levels of need. Future research should examine the implementation of MAPs in Scotland in a range of service contexts to understand their effectiveness in addressing harms and promoting wellbeing for those experiencing AUDs and homelessness.